INVESTIGATING TARGET TRACKING PROBLEM USING A SIMPLE DECORRELATION SCHEME - Choudhry, M. A.; Ali, K.; Hanif, A.; Mahmood, T. (The Nucleus, 2012)
The target tracking problem for radar by using extended Kalman filter is investigated in this research work. First of all, we have investigated the problem of target tracking in Cartesian coordinates with polar measurements. To compensate for the non-linearity existing due to Cartesian to polar coordinate transformation, the extended Kalman filter is employed to get the state estimate of the target. In most of the modern radars, the measurement frequency is much higher thus, causing correlation in the measurement errors. If this correlation is not considered in the measurement model then the tracking performance will certainly degrade. The Kalman filter equations need to be modified while taking correlated noise into account. There are different techniques available for de-correlation of colored noise. A simple de-correlation scheme is proposed for tracking target which is also undergoing maneuver due to atmospheric turbulence. Simulation results show that significant improvement in tracking performance is obtained considering noise correlation.